ISOLASI PROTEIN BIJI LAMTORO GUNG (Leucaena leucocephala) MENGGUNAKAN CAIRAN RUMEN DOMBA (Jurnal Teknologi Pangan, 2015)
Abstract Proteins are needed in the community, either as a direct intake in the body and is used in food products to improve their quality. Proteins in food can be isolated using several methods, one can use the method of enzymatic hydrolysis. The purpose of this study was to determine the effect of enzyme concentration and rumen fluid incubation time of the protein content and functional properties. This research was conducted using a variable 2 factors: The first factor enzyme concentrations: 0%, 40%, 80% and 100%. Factor II incubation time: 24 hours and 48 hours. The higest yield protein results was obtained Leucaena gung seed protein concentrates on the concentration of enzyme treatment of rumen fluid (10ml / 100g) and a 24-hour incubation time has a dry weight protein content 56.30%, on oil absorption capacity of 1.58 ml / g, the power of froth 11 , 56%, while for the water absorption of 3.42 ml / g, a density of 0.56 g Kamba / ml, the power emulsion 52.75%, water content 6.39% best results obtained from the treatment of the sheep rumen fluid concentrations of enzyme (10ml / 100g) and incubation time of 48 hours Keywords: Proteins, enzymes rumen, Lamtoro gung, incubation   Abstract Protein banyak dibutuhkan dalam masyarakat, baik sebagai asupan langsung dalam tubuh maupun digunakan dalam produk pangan untuk meningkatkan kualitasnya. Protein dalam bahan pangan dapat diisolasi menggunakan beberapa metode, salah satunya dapat menggunakan metode hidrolisis enzimatis. Tujuan penelitian ini adalah untuk mengetahui pengaruh konsentrasi enzim cairan rumen domba dan lama inkubasi terhadap kadar protein dan sifat fungsional dari pekatan protein biji lamtoro gung. Penelitian ini dilakukan menggunakan variable 2 faktor, yaitu : Faktor I konsentrasi enzim : 0%, 40%, 80% dan 100%. Faktor II lama inkubasi: 24 jam dan 48 jam. Hasil penelitian terbaik didapatkan pekatan protein biji lamtoro gung tertinggi pada perlakuan konsentrasi enzim cairan rumen domba (10ml/100gr) dan lama inkubasi 24 jam memiliki kadar protein berat kering 56,30%, daya serap minyak 1,58 ml/gr, daya buih 11,56%, sedangkan untuk daya serap air 3,42 ml/gr, densitas kamba 0,56 gr/ml, daya emulsi 52,75%, kadar air 6,39% hasil terbaik didapatkan dari perlakuan konsentrasi enzim cairan rumen domba (10ml/100gr) dan lama inkubasi 48 jam. Kata Kunci: Protein, enzim rumen, Lamtoro gung, inkubasi